The Problem of Monogamy vs. Polygamy and Its Regulation in the Mosaic Law as well as in Later Jewish and Christian Commentaries - Ruff, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The essential difference between the Jewish and the Christian traditions is, that the Mosaic Law, the Torah has been regarded in Judaism as a legal and state-creating, constituent factor, i.e. as a source of law; whereas in the Christian tradition, in accordance with the strict hermeneutic specified in the epistles of the Apostle Paul, it is not binding on non-Jewish believers and is only of a teaching nature. All the other books of the Old Testament are understood by both traditions as commentaries of divine origin and authority for the correct interpretation of the Torah, while the rest of the Jewish commentary literature on the whole Old Testament from antiquity to the present is known collectively as rabbinic literature. A – Christian – commentary of the Torah is also the New Testament itself, which also has divine authority in the Christian tradition. Through the Pauline hermeneutic, the Mosaic Law could only have influenced indirectly the development of medieval European ecclesiastical and secular legal systems as wisdom literature and exemplary texts reinterpreted by the New Testament, and not as a direct source of law. This paper examines the question of monogamy and polygamy in Mosaic Law and its commentaries. The Torah suggests monogamy as an ideal state, while at the same time allowing polygamy both ethically and legally. Nowhere does the New Testament explicitly prohibit polygamy except in the case of presbyters. Therefore, there was already a debate on the issue even in antiquity, in the vast textual ocean of rabbinic tradition, but the clearly lenient Torah rules made the obligatory abolition of polygamy out of the question.